The Smoking Habituals on the Patients Undergoing Cataract Surgery - Özge, Cengiz; Yılmaz, Ayça; Çalıkoğlu, Mukadder; Yeşilli, Münevver (Fırat University, 2006)
Objectives: Cataract is the main cause of preventable blindness throughout the world, and it is known that various factors play roles in its development. The relationship between smoking and cataract development, which is examined for years, is important as smoking is a preventable factor. We aimed to determine the effect of smoking on cataract development. Materials and Methods: In this retrospective study, 237 cataract patients operated in the Ophthalmology Clinic of our hospital were evaluated. The ones having risk factors for developing cataracts other than advanced age were excluded and other 123 patients were included in the study. Clinical and laboratory characteristics of smoker and non-smoker patients were compared using appropriate statistical methods. Results: Seventy-six (61.8%) of these patients were males, and 47 (38.2%) were females. Fifty-four (43.9%) of all patients were smokers, and 69 (56.1%) were non-smokers. Mean ages were 64.9±9.1 years, mean cataract formation ages were 62.3±9.3 years, and mean cataract operation ages were 63.9±9.1 years in the smoking group; in the non-smoking group, mean ages were 73.1.9±7.5 years, mean cataract formation ages were 71.0±7.2 years, and mean cataract operation ages were 72.5±7.4 years respectively. Ages, cataract formation ages, and cataract operation ages were significantly higher in the non-smoking group compared to smoking group (p

Amaç: Katarakt dünya üzerinde en önemli önlenebilir körlük nedenidir. Katarakt oluşumunda çeşitli faktörlerin rol oynadığı bilinmektedir. Yıllardır araştırılan katarakt gelişimi ve sigara arasındaki ilişki özellikle önlenebilir bir faktör olması açısından önemlidir. Çalışmamızda sigara alışkanlığı ile katarakt gelişimi arasındaki ilişkiyi saptamayı amaçladık. Gereç ve Yöntem: Çalışmamızda hastanemiz Göz Hastalıkları kliniğinde opere edilen 237 katarakt hastası retrospektif olarak incelendi. Katarakt gelişimi için ileri yaş dışında belirlenen bir risk faktörü olan hastalar çıkartıldıktan sonra kalan 123 hasta çalışmaya alındı. Sigara içen ve içmeyen hastaların klinik ve laboratuar özellikleri uygun istatistiksel yöntemler kullanılarak değerlendirildi. Bulgular: Hastaların 76'sı (%61.8) erkek, 47'si (%38.2) kadındı. Çalışmaya alınan tüm hastaların 54'ü (%43,9) sigara içiyor, 69'u (%56,1) içmiyordu. Sigara içen hastaların yaş ortalamaları 64.9±9.1, katarakt başlama yaşı 62.3±9.3, ve katarakt operasyon yaşı 63.9±9.1 olarak bulundu. Sigara içmeyen hastalarda ise yaş ortalamaları 73.1±7.5, katarakt başlama yaşı 71±7.2 ve katarakt operasyon yaşı 72.5±7.4 olarak bulundu. Sigara içenlerde yaş, katarakt başlangıç yaşı ve operasyon yaşı sigara içmeyenlerde içenlere göre istatistiksel olarak anlamlı derecede yüksek bulundu (p
Katarakt Tanısı İle Opere Edilen Olguların Sigara Alışkanlık Durumlarının Değerlendirilmesi